(untitled) - Vardanega, Renata; Santos, Diego T.; Meireles, M. Angela A. (Pharmacognosy Reviews)
Extraction processes are largely used in many chemical, biotechnological and pharmaceutical industries for recovery of bioactive compounds from medicinal plants. To replace the conventional extraction techniques, new techniques as high‑pressure extraction processes that use environment friendly solvents have been developed. However, these techniques, sometimes, are associated with low extraction rate. The ultrasound can be effectively used to improve the extraction rate by the increasing the mass transfer and possible rupture of cell wall due the formation of microcavities leading to higher product yields with reduced processing time and solvent consumption. This review presents a brief survey about the mechanism and aspects that affecting the ultrasound assisted extraction focusing on the use of ultrasound irradiation for high‑pressure extraction processes intensification.
Keywords: Bioactive compounds; extraction; high‑pressure; process intensification; ultrasound